The prevalence of pathogenic bacteria and antimicrobial resistance in milk of Ettawa Grade goat - Andriani, A.; Suwito, W. (Journal of the Indonesian Tropical Animal Agriculture, 2018)
Ettawa Grade (PE) are potentially developed goats to produce milk and meat. Milk is food of animal that is rich in nutrients, but it is a perishable food easily contaminated by microorganisms. Contaminated pathogenic bacteria in milk can decrease the quality and has an organoleptic effect on milk, as well as endangers human health. Milk contaminated with bacteria antimicrobial resistance (AMR) in which is resistant to antibiotics, may adversely affect the response to treatment with antibiotics in humans when suffering from infectious diseases and using antibiotics in therapy. In this study Ettawa Grade's samples of fresh milk and other dairy products were taken from some of the goat farms in Yogyakarta Sleman district. The samples were tested for the presence of pathogenic bacteria and for its resistance to several kinds of antibiotics. In this study 35 Ettawa Grade's samples of fresh milk and other dairy products (fresh milk, milk powder, ice cream, and yoghurt) were taken from some of the goat farms in Sleman district-Yogyakarta. The samples were tested for the presence of pathogenic bacteria and for its resistance to several kinds of antibiotics. The result of the prevalence of pathogenic bacteria in goat fresh milk and other dairy products was 15% Escherichia coli and had multi resistance to multiple antibiotics, namely ampicillin, colistin sulphate, cefixime, kanamycin, oxytetracycline, tetracycline and sulfonamide.